Alterations in gut immunological barrier in SARS-CoV-2 infection and their prognostic potential - Eleftheriotis, Gerasimos; Tsounis, Efthymios P.; Aggeletopoulou, Ioanna; Dousdampanis, Periklis; Triantos, Christos; Mouzaki, Athanasia; Marangos, Markos; Assimakopoulos, Stelios F. (Frontiers in Immunology, 2023)
Although coronavirus disease 2019 (COVID-19) is primarily associated with mild respiratory symptoms, a subset of patients may develop more complicated disease with systemic complications and multiple organ injury. The gastrointestinal tract may be directly infected by SARS-CoV-2 or secondarily affected by viremia and the release of inflammatory mediators that cause viral entry from the respiratory epithelium. Impaired intestinal barrier function in SARS-CoV-2 infection is a key factor leading to excessive microbial and endotoxin translocation, which triggers a strong systemic immune response and leads to the development of viral sepsis syndrome with severe sequelae. Multiple components of the gut immune system are affected, resulting in a diminished or dysfunctional gut immunological barrier. Antiviral peptides, inflammatory mediators, immune cell chemotaxis, and secretory immunoglobulins are important parameters that are negatively affected in SARS-CoV-2 infection. Mucosal CD4+ and CD8+ T cells, Th17 cells, neutrophils, dendritic cells, and macrophages are activated, and the number of regulatory T cells decreases, promoting an overactivated immune response with increased expression of type I and III interferons and other proinflammatory cytokines. The changes in the immunologic barrier could be promoted in part by a dysbiotic gut microbiota, through commensal-derived signals and metabolites. On the other hand, the proinflammatory intestinal environment could further compromise the integrity of the intestinal epithelium by promoting enterocyte apoptosis and disruption of tight junctions. This review summarizes the changes in the gut immunological barrier during SARS-CoV-2 infection and their prognostic potential.